2015
DOI: 10.1038/srep10921
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Li/S Battery Electrodes On 3D Current Collectors Studied Using X-ray Phase Contrast Tomography

Abstract: Lithium/sulphur batteries are promising candidates for future energy storage systems, mainly due to their high potential capacity. However low sulphur utilization and capacity fading hinder practical realizations. In order to improve understanding of the system, we investigate Li/S electrode morphology changes for different ageing steps, using X-ray phase contrast tomography. Thereby we find a strong decrease of sulphur loading after the first cycle, and a constant loading of about 15% of the initial loading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 36 publications
3
74
0
Order By: Relevance
“…Recently, these X-ray synchrotron techniques have found widespread attention in the lithium ion battery research community123456789101112. While synchrotron X-ray diffraction techniques have been successfully applied to study the phase transformation mechanisms in LiFePO 4 olivine structures8111314 for example, tomographic microscopy was shown to be an excellent tool to track volumetric changes and the resulting crack formation and mechanical degradation mechanisms in alloy anodes upon electrochemical cycling4.…”
mentioning
confidence: 99%
“…Recently, these X-ray synchrotron techniques have found widespread attention in the lithium ion battery research community123456789101112. While synchrotron X-ray diffraction techniques have been successfully applied to study the phase transformation mechanisms in LiFePO 4 olivine structures8111314 for example, tomographic microscopy was shown to be an excellent tool to track volumetric changes and the resulting crack formation and mechanical degradation mechanisms in alloy anodes upon electrochemical cycling4.…”
mentioning
confidence: 99%
“…25 Due to the high fluxes generated by synchrotron sources, synchrotron X-ray imaging has evolved into a powerful characterization tool in the field of materials science. [26][27][28][29][30][31][32][33][34][35][36] Especially synchrotron X-ray tomography has enabled researchers to obtain unprecedented insights into LIBs from the level of individual particles to the scale of entire electrodes. [37][38][39][40] Most recently, Ebner et al, have directly observed and quantified electrochemical and mechanical degradation in a SnO anode.…”
Section: Introductionmentioning
confidence: 99%
“…Charge capacities of 1027 mAh g -1 and 560 mAh g -1 were obtained for NWC and Al based electrodes respectively, with irreversible capacity loss of ~ 8 % for both cells. In the second cycle, the upper discharge plateau is shifted to higher potential value (2.4 V), which could be explained, as previously reported, 26 by active material reorganization and improved electrode conductivity after first step of sulfur dissolution/formation. In addition, initial cell overpotential may depend on the lithium surface and its resistive passivation layer, which may be improved after first lithium stripping/plating cycle too.…”
Section: Resultsmentioning
confidence: 55%
“…4b,d, left), therefore confirming the fact that the active material (sulfur or Li 2 S) spreads onto the NWC current collector upon cycling. 26 However, according to our previous report, 26 the largest fraction of sulfur was located on the top of the electrode, where the ink was deposited. This result was in accordance with the higher active surface area of Super P® conductive additive than NWC one.…”
Section: Resultsmentioning
confidence: 95%